2000
DOI: 10.1021/tx0000825
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Lamotrigine to a Reactive Arene Oxide Intermediate

Abstract: Lamotrigine [3,5-diamino-6-(2,3-dichlorophenyl)-1,2,4-triazine] is an antiepileptic drug associated with hypersensitivity reactions which are thought to be an immunological response to metabolically generated drug-protein adducts. The o-dichlorophenyl moiety is a potential site for bioactivation of the drug to an arene oxide. The metabolites of [(14)C]lamotrigine (78 micromol/kg, iv) in adult male Wistar rats were characterized with particular reference to thioether derivatives of an epoxide intermediate. Bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 32 publications
6
60
0
Order By: Relevance
“…The major drugrelated components detected in control mouse urine were the parent lamotrigine and lamotrigine N-oxide, as reported earlier in rats ( Fig. 2B; (Parsons and Miles, 1984;Maggs et al, 2000). The small amounts of radioactivity excreted in the bile of both chimeric and control mice were comprised largely of unchanged lamotrigine (data not shown).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The major drugrelated components detected in control mouse urine were the parent lamotrigine and lamotrigine N-oxide, as reported earlier in rats ( Fig. 2B; (Parsons and Miles, 1984;Maggs et al, 2000). The small amounts of radioactivity excreted in the bile of both chimeric and control mice were comprised largely of unchanged lamotrigine (data not shown).…”
Section: Resultssupporting
confidence: 82%
“…Similar to many other tertiary amine drugs that form quaternary ammonium glucuronides, formation of the lamotrigine N-2 glucuronide appears to be restricted to monkeys and humans and is not observed to a significant extent in rodents (Green et al, 1995;Luo et al, 1995;Hawes, 1998). In rats, lamotrigine is eliminated largely via urinary excretion of the intact parent drug and, to a lesser extent, via N-2-oxidation (to form an N-oxide) and sequential epoxidation and glutathione conjugation of the O-dichlorophenyl ring (Parsons and Miles, 1984;Maggs et al, 2000). This species difference in the formation of quaternary ammonium glucuronides appears related to the fact that this metabolic pathway is catalyzed by the UGT1A4 enzyme, which is a pseudogene in rodents (Green et al, 1995;Green and Tephly, 1998;Ogura et al, 2006;Argikar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found convincing evidence of a glutathione conjugate of lamotrigine in rat bile, which was presumed to be formed from a reactive arene oxide (Maggs et al, 2000). However, no phenol metabolites were detected in humans (Doig and Clare, 1991), and in general phenols are one of the major downstream products of arene oxides.…”
mentioning
confidence: 95%
“…The symptoms can include fever, skin rash, agranulocytosis, and lymphadenopathy (Schlienger et al, 1998). There appears to be an association between the formation of reactive metabolites and the risk that a drug will cause idiosyncratic drug reactions (Maggs et al, 2000). The two major hypotheses that have been used to link the formation of reactive metabolites and idiosyncratic drug reactions are the hapten hypothesis and the danger hypothesis (Uetrecht, 1999).…”
mentioning
confidence: 99%
“…For example, in the rat, lamotrigine, a drug used in the management of epilepsy syndromes, was metabolized primarily by thioether addition to a reactive intermediate arene oxide, yielding the glutathione conjugate of dihydrohydroxylamotrigine. Unlike the DHSG conjugate of MK-0767, the DHSG conjugate of lamotrigine is unstable and spontaneously dehydrates and rearomatizes at room temperature or upon freezing and thawing (Maggs et al, 2000). Similarly, 1,2-dichlorobenzene was metabolized to dichlorocyclohexadiene epoxide, which underwent glutathione addition followed by the spontaneous loss of water to generate the glutathione conjugate of dichlorobenzene (Hissink et al, 1996).…”
Section: Downloaded Frommentioning
confidence: 99%